2003
DOI: 10.1016/j.ydbio.2003.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a secreted BMP antagonist, ectodin, integrating BMP, FGF, and SHH signals from the tooth enamel knot

Abstract: We have identified mouse and human cDNAs encoding a novel secreted BMP inhibitor, which we have named ectodin. It is most homologous (approximately 37% amino acid identity) to sclerostin that is a secreted BMP antagonist. Recombinant ectodin protein produced in cultured cells was efficiently secreted as a antagonist. Ectodin inhibited the activity of BMP2, BMP4, BMP6, and BMP7 for mouse preosteoblastic MC3T3-E1 cells, and bound to these BMPs with high affinity. Ectodin is intensely expressed in developing ecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
228
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 240 publications
(238 citation statements)
references
References 50 publications
9
228
0
1
Order By: Relevance
“…It is interesting to note that the expression of follistatin is complementary to ectodin, a recently identified BMP inhibitor that is down-regulated in the enamel knot and surrounding tissue (Laurikkala et al, 2003). The inhibition of ectodin expression was regulated by Shh and FGF, presumably from the enamel knot.…”
Section: Follistatin Regulates the Cusp Patterning Of Molar Teethmentioning
confidence: 97%
See 1 more Smart Citation
“…It is interesting to note that the expression of follistatin is complementary to ectodin, a recently identified BMP inhibitor that is down-regulated in the enamel knot and surrounding tissue (Laurikkala et al, 2003). The inhibition of ectodin expression was regulated by Shh and FGF, presumably from the enamel knot.…”
Section: Follistatin Regulates the Cusp Patterning Of Molar Teethmentioning
confidence: 97%
“…Misregulation of TGF␤ signaling often results in congenital defects as well as cancer and other diseases (Chang et al, 2002;Gumienny and Padgett, 2002). The extracellular inhibitors of BMPs include noggin, chordin, DAN/Cerberus, sclerostin, ectodin and follistatin (Balemans and Van Hul, 2002;Laurikkala et al, 2003). Follistatin is a secreted protein that was originally identified as an activin-antagonizing protein (Nakamura et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…In other species, this protein is known as USAG-1 (Rattus norvegius; Yanagita et al, 2004), ectodin (Mus musculus; Laurikkala et al, 2003;Kassai et al, 2005), and wise (Xenopus laevis; Itasaki et al, 2003). Recent mouse knockouts of ectodin/USAG-1 have shown that this molecule is important in tooth formation and modulation of the renoprotective effects of BMP-7 (Kassai et al, 2005;.…”
Section: Introductionmentioning
confidence: 99%
“…The Xenopus publication described a context-dependent activator and inhibitor of Wnt signaling (given the name Wise) that acted by binding to LRP6, a protein closely related to LRP5. (29) Wise, also known as ectodin, (30) USAG-1, (31) and SOSTDC1, is most closely related to sclerostin, and together they make up the two-member sclerostin family. These interesting findings in Xenopus, coupled with the sclerostin and LRP5 genetic data, strongly suggested that sclerostin acted at the molecular level, at least in part, by binding to LRP5.…”
mentioning
confidence: 99%